The joy of missing out : live more by doing less - Dalton, Tonya (Nelson Books, an imprint of Thomas Nelson, 2019)
Productivity expert and CEO of inkWELL Press Productivity Co. Tonya Dalton challenges women to rethink "busy" and intentionally live with a mind-set of abundance. Overwhelmed. Too many women are swamped and exhausted by all they strive to do, ending most days feeling unsatisfied and unsuccessful. Tonya Dalton, productivity expert and CEO of inkWELL Press Productivity Co., offers these women a liberating shift in perspective: Feeling overwhelmed isn't the result of having too much to do - it's from not knowing where to start. In her highly anticipated first book, Dalton inspires women to reject the pressure to do more, be more, and achieve more. She shows them how to focus on what's important to them and then helps them develop their own unique productivity systems. Through her proven liveWELL Method, Dalton provides actionable strategies with relevant exercises that help women to discover their purpose, clarify their priorities, simplify their lives, and finally achieve harmony by embracing the "unbalance" that is inherent in their lives. As a result, women discover they can finally live guilt-free, abundant lives--because living a life centered around their priorities results in more satisfaction and success, both at work and at home.